Wordtune as an Artificial Intelligence (AI) Powered English Writing Assistant: EFL Students Perception as Alternative to Write English - Amanda; Utami Dewi (Institut Agama Islam Negeri Ponorogo, 2025)
Currently, the adoption of AI-driven writing tools is becoming increasingly widespread among users. Particularly for EFL students, these AI applications offer significant advantages. The aim of this article is to explore students' perceptions of Wordtune as an alternative tool for writing in English. This research employs a qualitative approach to examine how students view Wordtune in their English classes. There are 30 Indonesian undergraduate students majoring in English education used Wordtune as participants. The Data was gathered through questionnaires and in-depth interviews, which were analyzed through percentage and thematic content analysis. The results of the study showed that students have several positive perceptions of Wordtune as an assistant in writing, including, Wordtune speeds up writing, easily fixes grammar issues, provides word options, inspires new ideas, improves revision quality, and user-friendly. With this study, students are expected to be able to apply it in learning activities related to writing English thus that the writing results produced are better and more structured.